Laparoscopic common bile duct exploration with antegrade stenting – A case report with review of literature - Kaur, Ravneet; Joshi, Abhijit Sharadchandra (Eastern Journal of Medical Sciences, 2025)
Endoscopic retrograde cholangiopancreatography (ERCP) is the preferred therapeutic modality for treating common bile duct (CBD) stone/s. It has since evolved significantly with the progressive refinement of endoscopes, endoscopic accessories, and endoscopic techniques, becoming a standardized effective procedure that has benefited many patients with choledocholithiasis. Many international surgical publications have also underscored the important, effective, and pragmatic role played by common bile duct exploration surgery as a valid alternative to endo-therapy; from time to time. These papers pitch surgery as the first therapeutic option over endoscopy for bile duct stones. But in the majority of the health care institutions around the world, endo-therapy is the preferred first step. However, it is a highly advanced procedure which can sometimes fail due to various reasons – technical, logistical, or anatomical. In such cases, a redo is usually attempted after 48 hours. If this also does not succeed, a surgical exploration of the common bile duct (open, laparoscopic, or robotic) may be required for choledocholithiasis. Herein, the authors describe one such case of a 75-year- old gentleman who presented with cholelithiasis and choledocholithiasis. During the initial two attempts at ERCP made by the gastroenterologist, deep selective cannulation of the CBD could not be achieved. It was then decided to perform a laparoscopic CBD exploration and cholecystectomy. The surgery and postoperative recovery was uneventful, and over a 1-year postoperative period, the patient remains asymptomatic.